Exploring the restorativeness of different hydrodynamic landscapes in world natural heritage sites - Zhang, Ping; Zhang, Tongyao; Chen, Zexuan; He, Qianyi; Luo, Ke; Li, Jinpeng; Yang, Yanbin; Zhang, Qingjie; Wang, Xuan; Han, Limin; Chen, Mingze; Zhao, Fupei; et al. (Frontiers in Child and Adolescent Psychiatry, 2025)
Audiovisual environmental perception has been the focus of numerous empirical studies. This study employs virtual reality (VR) to explore how different hydrodynamic waterscapes in Jiuzhaigou World Natural Heritage Site affect physiological and psychological restoration in youth. According to the results, audiovisual interactions, particularly with water sounds and birdsongs, significantly enhance physiological restoration compared to visuals alone. High-intensity hydrodynamic landscapes, regardless of birdsongs, exhibit the highest physiological restoration. There is a linearly positive correlation between physiological restorativeness and hydrodynamic landscapes. Medium-intensity hydrodynamic landscapes with rich forms are most psychologically restorative. In low-medium-intensity settings, visuals contribute more to psychological restoration than soundscapes. It is further found that waterscapes rich in flora and fauna feature a higher level of biodiversity. In the waterscapes with both elements of vegetation and water, the restorativeness of plant and animal resources is greater than that of water. This work highlights the need to focus on the application of different hydrodynamic landscapes in urban areas and the conservation of World Heritage Sites.